Analisis SiLPA Sebagai Alat Ukur Pengelolaan APBD pada Dinas Perindustrian dan Perdagangan Kabupaten Blitar - Amelia, Fitri; Khoiriawati, Novi (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2022)
Funds and Budget Calculation Excess Remaining (SiLPA) is the difference in funding from the realization of the revenues and expenditures for one period. The existence of SILPA in a period indicates the excess remaining financing in that period. The objective of this research was to analyze the performance of APBD management and found out the causes of SILPA in the period 2016 – 2020. This research was carried out at the Department of Industry and Trade of Blitar Regency using descriptive qualitative methods. Data collection techniques were carried out by observation, interviews, and documentation. The results showed that the performance of APBD management was good and efficient. Meanwhile, the existence of SILPA was due to the efficiency of spending and exceeding income. Keywords : APBD, SiLPA